Analisis Pasal 6 Standar Kompetensi Lulusan Permendikbudristek No.53 Tahun 2023 terhadap Transformsi Pendidikan Agama Kristen Di Indonesia (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study analyzes the implications of Article 6 of the Graduate Competency Standards (SKL) in Permendikbudristek No. 53 of 2023 on the transformation of Christian Religious Education (PAK) in Indonesia. Using a qualitative approach and document analysis method, this study explores the alignment between national education policies and the objectives of Christian Religious Education (CRE) in shaping students' character based on Christian values. The main data were obtained from the text of Permendikbudristek No. 53/2023, the PAK curriculum, as well as supporting documents such as church guidelines and national education standards. The research results indicate that although the Graduate Competency Standards (SKL) are oriented towards strengthening the Pancasila Student Profile, there are opportunities to integrate Christian faith values within the framework of graduate competencies. However, challenges arise in adjusting the learning methodologies and evaluations while maintaining the distinctiveness of PAK. This study recommends the development of a contextual, collaborative, and responsive PAK model to national education policies without neglecting its spiritual mission.